Changes in Nurses’ Knowledge Before and After Being Given Evidence-Based Nursing Education Through Video Conference - Bahlail, Rezka; Somantri, Irman; Nurhakim, Furkon (Media Karya Kesehatan, 2024)
Professional nurses are expected to be able to apply Evidence-Based Nursing (EBN) in the nursing process. However, the facts state that nurses are not used to applying EBN. This study aimed to determine changes in nurses' knowledge about EBN before and after being given education about EBN through video conference. This research is quantitative descriptive. Method using a pre-experimental design with the design of one group pre-test and post-test through PKM program at the general hospital in Bandung. 25 nurses participated in this study taken from the number of participants who attended. The results showed an increase in pre-test and post-test scores during lectures on EBN with Sig 2 tailed value 0.00 < 0.05. Although there was increase of 14.80 in nurses’ knowledge about EBN, video conference has weaknesses when used as a learning media. One of the weaknesses is unstable internet network constraints which had an impact on the quality of learning received by participants. Keywords: Evidence-based nursing, nurses, video conference